Immunohistochemical Detection of Porcine Reproductive and Respiratory Syndrome Virus Antigen in Formalin-Fixed, Paraffin-Embedded Tissues with Correlation to Clinicopathologic Data - Manzano, Lavina Gracia G. (KnE Life Sciences, 2017)
Immunohistochemistry (IHC) was used in this study to detect the presence of porcine reproductive and respiratory virus (PRRSV) antigen using monoclonal antibody (Mab SDOW17) in formalin-fixed, paraffin embedded tissues of lung, lymph node, heart, spleen, and kidney of pre- weaning to less than 90 day old pigs. Out of the 25 tissue samples examined from swine cases of the Philippine Animal Health Center (PAHC), Bureau of Animal Industry and College of Veterinary Medicine (CVM) Histopathology Laboratory, University of the Philippines-Los Baños (UPLB), 14 or 56% (14/25) were IHC positive for PRRSV antigen. Among the selected tissue samples, the PRRS virus was detected the most in the lymph nodes (64%) and lungs (40%), respectively, compared to other organs such as spleen (33%), kidney (28%), and the heart (17%). Only 43% (6/14) of cases coincided with the pathogenesis and clinicopathologic lesions of PRRS which are proliferative interstitial pneumonia and lymphoid follicular hyperplasia and necrosis. PRRS positive cases in IHC were consistently found to have co-infections with viral and bacterial diseases. Since PRRSV has tropism for macrophages and destruction of these cells leads to immunosuppression, affected animals are vulnerable to secondary infections. Keywords: formalin-fixed; immunohistochemistry; paraffin embedded tissue; piglets; Porcine Reproductive and Respiratory Syndrome; PRRS virus antigen; Mab SDOW17